2013
DOI: 10.1161/circulationaha.113.003862
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Complications Associated With Catheter Ablation of Atrial Fibrillation in the United States Between 2000 and 2010

Abstract: Background-Atrial fibrillation ablation has made tremendous progress with respect to innovation, efficacy, and safety.However, limited data exist regarding the burden and trends in adverse outcomes arising from this procedure. The aim of our study was to examine the frequency of adverse events attributable to atrial fibrillation (AF) ablation and the influence of operator and hospital volume on outcomes. Methods and Results-With the use of the Nationwide Inpatient Sample, we identified AF patients treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
381
10
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(428 citation statements)
references
References 23 publications
27
381
10
10
Order By: Relevance
“…242,489,503,532,533,655,673,796,798,799,806,920,921,1202,1203,1204 More than two-thirds of the clinical trials reviewed for preparation of this document reported one or more cerebrovascular events. Thromboembolic events typically occur within 24 hours of the ablation procedure, with the high-risk period extending for the first 2 weeks following ablation.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…242,489,503,532,533,655,673,796,798,799,806,920,921,1202,1203,1204 More than two-thirds of the clinical trials reviewed for preparation of this document reported one or more cerebrovascular events. Thromboembolic events typically occur within 24 hours of the ablation procedure, with the high-risk period extending for the first 2 weeks following ablation.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
“…921 Awareness about the risk of death and the possible causes might help physicians set more appropriate and efficient standards for procedural safety, and need to be considered in the patient’s decision-making process.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
“…Data have consistently shown 107,108 that procedural outcomes improve with center experience. U.S. registry data from over 93,000 patients in the U.S. national inpatient sample database 5 showed an in-hospital mortality rate of 0.42%, and an overall complication rate of 6.29% (figure 4) that were lower in high volume centers. The possibility that complication rates are trending higher in some studies 5 , although not others [107][108][109][110] , may reflect treatment of more complex, older patients with persistent AF 111 in whom widespread ablation and long procedure times may cause complications.…”
Section: Complications Of Af Ablationmentioning
confidence: 99%
“…The use of ablation has been encouraged by the disappointing results of important trials that question both pillars of pharmacological therapy -to strictly control ventricular rate 2 or to maintain sinus rhythm 3,4 . Buoyed by the success of ablation for 'simple' supraventricular and ventricular arrhythmias, ablation is increasingly used for AF 5 and is superior to pharmacological therapy for patients with early (paroxysmal) 6,7 to advanced (persistent) AF 8 . Nevertheless, fibrillation is a complex disease and the overall success of ablation remains lower 9 for AF than for other arrhythmias 6, 7, 10-13 -despite remarkable successes in individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…Catheter ablation (CA) of AF is commonly employed to reduce arrhythmia burden, manage symptoms, and improve AF-specific quality of life [2]. Although CA is highly effective in some patients, AF recurrence after ablation occurs in up to 65% of patients undergoing this procedure within 1 year [2].…”
Section: Introductionmentioning
confidence: 99%